The bridge across forever - Richard Bach (A Dell Book, 1984)
The author of "Jonathan Livingston Seagull" recounts his search for his dreamed-of soulmate, his detour into wealth and success, and his ultimate meeting with the woman with whom he has found new and intense love and enchantment
Keywords: Autobiographies -- Autobiographies; Biographies -- Biographies